Everybody says it, so... It must be true? Folklore and common knowledge evidentiality: From theory to sociopragmatic research - Cestero Mancera, Ana María; Kotwica, Dorota (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This paper sets out the theoretical approaches, methodology and preliminary results of the study of folklore or common knowledge evidentiality in the PRESEEA corpus of semi-directed interviews. The category under study is related to the knowledge shared in speech communities, widely held beliefs and popular wisdom. It is considered that the use of folklore evidence mechanisms is highly strategic. The aims of this study are, on the one hand, to ascertain the functional performance and linguistic-pragmatic patterns of this type of evidence, and, on the other and most importantly, to document and analyse sociopragmatic and geolectal patterns in the use of the resource. This paper sets out the theoretical basis and methodology of the research and offers the first comparative results obtained in the initial coordinated studies carried out within the framework of the PRESEEA macro-project: shared repertoire or folklore evidentiality in the speeches of Madrid and of Valencia.
Keywords: corpus analysis; methodology; evidentiality; PRESEEA; mitigation; argumentative reinforcement